Assessment of the factors affecting the efficiency of yellow corn farmers in selected provinces in the Philippines (2019)
The paper is an empirical study of the technical efficiency of yellow corn farmers in selected provinces of the Philippines using cross section data from 154 corn farmers. It aimed to determine the level of input utilization, profitability of yellow corn and determine the factors affecting corn productivity and technical efficiency. A Stochastic Frontier Production Function Model through maximum likelihood estimation (MLE) Method was used to estimate farm-level technical efficiency. Analysis showed that, on the average, yellow corn farmers used 91.7 kilogram of seeds; applied 224 kilograms of nitrogen, 49 kilograms of Phosphorous, 9 kilograms of Potassium; and applied PhP 3,039 worth of agro -chemicals in one production season. The results also showed that the average technical efficiency of yellow corn farmers was 67.6 percent. It was found that the amount of seeds, nitrogen and potassium fertilizers, and agro-chemicals used are significant factors influencing the productivity of yellow corn in the study areas. Moreover, factors such as the level of education of the farmers; years of farmers’ experience in yellow corn production; and training and seminars attended by the farmers showed positive effects on the farm-level technical efficiency of yellow corn farms.
Keywords: Corn farmers; Crop productions; Labor productivity; Yellow corn